Phytochemical analysis of some medicinal plants - Yadav, RNS; Agarwala, Munin (Journal of Phytology, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> North-eastern India has been known for its rich biological diversity. For this study, seven medicinal plants such as Bryophyllum pinnatum, Ipomea aquatica, Oldenlandia corymbosa, Ricinus communis, Terminalia bellerica, Tinospora cordifolia, and Xanthium strumarium, were selected. The aim of the present study was to investigate the presence of phytochemicals and to determine the total phenolic and flavonoid contents of the selected medicinal plants. Soxhlet apparatus was used for the organic solvent extraction. Solvents used were water, methanol, ethanol, and acetone. Total phenolic contents of the aqueous extracts of the plants were determined by the Folin-Ciocalteus reagent method whereas total flavonoid contents of the aqueous extracts were determined by the Aluminium Chloride method. Proteins, carbohydrates, phenols, tannins, flavonoids, saponins, were detected in all of the plants tested. Total phenolic contents obtained were 18.4mg/gm, 18.8mg/gm, 11.6mg/gm, 29.2mg/gm, 29.6mg/gm, 40.8mg/gm, 12.8mg/gm, 71.6mg/gm of the extract and total flavonoid contents obtained were 8.4mg/gm, 37.6mg/gm, 4.4mg/gm, 6mg/gm, 42.8mg/gm, 18mg/gm, 6mg/gm, 28.8mg/gm of the extract for the plants Bryophyllum pinnatum (Leaves), Ipomea aquatica (Leaves), Oldenlandia corymbosa (Whole plant), Ricinus communis (Roots), Terminalia bellerica (Leaves), Tinospora cordifolia (Leaves), Tinospora cordifolia (Stem), and Xanthium strumarium (Leaves) respectively. Our findings provided evidence that crude aqueous and organic solvent extracts of these tested plants contain medicinally important bioactive compounds and it justifies their use in the traditional medicines for the treatment of different diseases.